Correlation Between Gram Negative Bacterial Colonization, Environmental Contamination and the Development of Infections at Intensive Care Unit: Colonization and Environmental Contamination in Intensive Care Unit (Biological Sciences - PJSIR, 2024)
Detection of the source of infection by multidrug resistant gram-negative bacteria (MDR-GNB) may help in the development of effective treatment protocols resulting in improved patient outcomes. The aim of this study was to determine the prevalence of MDR-GNB colonization and infection among patients in ICU and the association between colonization, environmental contamination and infections. Throat swabs were taken from 165 ICU patients within 48 h of admission. Then clinical samples were collected from those patients who developed infections according to the site of infection. Also, weekly environmental samples were obtained from the occupied partition in ICU. Throat colonization by GNB was detected in only 6.06%. About 27 (16%) out of the admitted patients got infections and only 9 patients (5.45%) had hospital acquired infections (HAIs). The rate of environmental contamination due to GNB during the studied period (8 weeks) which was 27.06%. MDR-GNB isolates represented 50% of gram-negative isolates recovered from colonized patients and 86.11% from infected patients and 58.08% from environmental samples. Klebsiella pneumoniae (K. pneumoniae) was the predominant isolate recovered from both colonized and infected patients (50.00% and 38.89% respectively) as well as from environmental samples (48.29%). Extended spectrum beta lactamases (ESBL) and carbapenem resistance were predominant among pneumoniae isolates from clinical and environmental samples. High rate of cross contamination between infected patients and their occupied environment was detected among K. pneumoniae and Acinetobacter baumannii complex (Acb complex) isolates.